Memory, Mimesis, and the Modern: The Literary Heritage in Māmayh’s Poetry - Masarwa, Alev (TESTINSTANZ: Wissenschaftliche Schriften der Universität Münster, 2022)
Māmayh ar-Rūmī ad-Dimašqī was one of the most significant Damascan poets in the 10th/16th century, whose verses were sung from Damascus to Yemen. Based on the current results of the ongoing edition of Māmayh's dīwān (Rawḍat al-muštāq wa-bahǧat al-ʿuššāq "Garden of the ardent yearner and the joy of the lovers") this study discusses a selection of poems in which the poet converses with the literary past by not only using mimetic and emulative techniques (like taḍmīn, iqtibās, and taḫmīs poems) but also through the use of more modern styles, forms and topics (like ʿāṭil verses, coffee poems, and vernacular poems). While the mimetic poems refer directly to the admired or canonized models of the past perpetuating the tradition into the poet's present, the focus of the contemporary topics in the dīwān is on how the poet's present is connected to the poetic and aesthetic practices of the past. With the analysis of Māmayh’s poetry, the study offers evidence of the impressive literary and intellectual background of an initially Ottomanized and then 'Syrianized' (former soldier-) poet, as well as his tremendous poetic creativity in melding together the 'old' and the 'new' in his verse. Permalinkhttps://nbn-resolving.org/urn:nbn:de:hbz:6-33069638049 ISBN978-3-487-16216-4 (Druckausgabe Georg Olms Verlag)978-3-8405-0274-3 (elektronische Version) Paperback, 81 Seiten